Control of signaling alignment during the dynamic courtship display of a jumping spider. (22nd August 2017) - Echeverri, Sebastian A; Morehouse, Nathan I; Zurek, Daniel B
Abstract : Effective signaling depends on the relative positions of signaler and receiver, but do both parties always position themselves ideally? Which party drives this interaction? Female jumping spiders assess a courting male's coloration, but can only see a male's colors when both are facing each other. The female drives the courtship interaction by frequently turning away from the male. The male must capture her attention, and only presents certain display elements when he has it. Abstract: During communication, alignment between signals and sensors can be critical. Signals are often best perceived from specific angles, and sensory systems can also exhibit strong directional biases. However, we know little about how animals establish and maintain such signaling alignment during communication. To investigate this, we characterized the spatial dynamics of visual courtship signaling in the jumping spider Habronattus pyrrithrix . The male performs forward-facing displays involving complex color and movement patterns, with distinct long- and short-range phases. The female views displays with 2 distinct eye types and can only perceive colors and fine patterns of male displays when they are presented in her frontal field of view. Whether and how courtship interactions produce such alignment between male display and female field of view is unknown. We recorded relative positions and orientations of both actors throughout courtship and established the role of each sex in maintaining signaling alignment. Males always oriented their displays toward the female. However, when females were free to move, male displays were consistently aligned with female principal eyes only during short-range courtship. When female position was fixed, signaling alignment consistently occurred during both phases, suggesting that female movement reduces communication efficacy. When female models were experimentally rotated to face away during courtship, males rarely repositioned themselves to re-align their display. However, males were more likely to present certain display elements after females turned to face them. Thus, although signaling alignment is a function of both sexes, males appear to rely on female behavior for effective communication.